Inclusive Curriculum Based on Islamic Values in Building Independent Character in Children with Special Needs - Habibi Muhammad, Devy; Khozin, Khozin; Humaidi, M. Nurul (LPPPIPublishing, 2024)
This study aims to analyze the inclusive curriculum in developing independent character in the aspects of aqidah, worship (ibadah), and noble character (akhlak mulia) for individuals with special needs. Children with special needs require a learning approach that is effectively integrated with the community. This integration is crucial not only for their ability to interact with their surroundings but also for acquiring essential life skills and reaching their optimal potential. The study adopts a descriptive qualitative approach. The findings reveal that the inclusive curriculum at SPS Permata Probolinggo emphasizes the development of independent character in students with special needs through the application of Islamic values, including aqidah, ibadah, and akhlak mulia. The curriculum is designed based on national education laws and adapted to meet the needs of students, aiming to enhance their cognitive, socio-emotional abilities, and life skills. Learning is conducted using a